ZIKA VIRUS INFECTION; VERTICAL TRANSMISSION AND FETAL CONGENITAL ANOMALIES - Abbasi, Aziz-un-Nisa (Journal of Ayub Medical College Abbottabad, 2016)
Zika virus (ZIKV) is an arbovirus belonging to flaviviridae family that includes Dengue, West Nile, and Yellow Fever among others. Zika virus was first discovered in 1947 in Zika forest of Uganda. It is a vector borne disease, which has been sporadically reported mostly from Africa, Pacific islands and Southeast Asia since its discovery. ZIKV infection presents as a mild illness with symptoms lasting for several days to a week after the bite of an infected mosquito. Majority of the patients have low grade fever, rash, headaches, joints pain, myalgia, and flu like symptoms. Pregnant women are more vulnerable to ZIKV infection and serious congenital anomalies can occur in foetus through trans-placental transmission. The gestation at which infection is acquired is important. ZIKA virus infection acquired in early pregnancy poses greater risk. There is no evidence so far about transmission through breast milk. Foetal microcephaly, Gillian Barre syndrome and other neurological and autoimmune syndromes have been reported in areas where ZIKA outbreaks have occurred. As infection is usually very mild no specific treatment is required. Pregnant women may be advised to take rest, get plenty of fluids. For fever and pain they can take antipyretics like paracetamol. So far no specific drugs or vaccines are available against ZIKA Virus Infection so prevention is the mainstay against this diseases. As ZIKV infection is a vector borne disease, prevention can be a multi-pronged strategy. These entail vector control interventions, personal protection, environmental sanitation and health education among others.